Polypoidal choroidal vasculopathy in exudative and haemorrhagic pigment epithelial detachments. Issue 5 (1st May 2000) - Ahuja, Richard M; Stanga, Paulo E; Vingerling, Johannes R; Reck, Anne C; Bird, Alan C
Abstract : AIMS: To determine the prevalence of polypoidal choroidopathy in consecutive patients presenting with large haemorrhagic and exudative neurosensory retinal and retinal pigment epithelial detachments (PEDs) of over 2 mm in diameter in the absence of drusen. METHODS: 40 patients were identified over a 5 month period of which 29 had haemorrhagic detachments, and 11 had purely exudative detachments. All had indocyanine green (ICG) angiography, and the presence was sought of large blood vessels in the choroid associated with localised dilated terminals that filled slowly and leaked ICG. RESULTS: In 34 cases (85%) there was an appearance consistent with previous descriptions of idiopathic polypoidal choroidal vasculopathy. Of the six without polypoidal lesions the disorder was attributed to choroidal neovascularisation in four, chorioretinitis in one, and a fibrovascular PED in one. Of those with polypoidal lesions 20 (65%) were female, the mean age was 65.4 years (range 44–88), and 25 (74%) were white, seven (20%) black, and two (6%) east Asian. Eight had a history of hypertension. Visual acuity varied from 6/6 to counting fingers in the involved eye (mean 6/24). Bilateral polypoidal choroidal lesions were demonstrated in 16 patients (47%). The predominant location for these lesions was the macular region in 23 patients (68%). Polypoidal vasculopathy was found in 16 patients (47%) who had a previous diagnosis of age related macular disease (AMD). No patients had evidence of intraocular inflammation. CONCLUSIONS: In a largely white patient population a high proportion of patients with haemorrhagic and exudative PEDs has evidence of polypoidal lesions on ICG angiography.